2017
DOI: 10.2196/resprot.6449
|View full text |Cite
|
Sign up to set email alerts
|

Workability and Muscle Strength in Patients With Seropositive Rheumatoid Arthritis: Survey Study Protocol

Abstract: BackgroundRheumatoid arthritis (RA) and other rheumatic conditions not only fundamentally affect patients’ quality of life and physiological needs but are also negatively associated with work ability. The costs of poor work ability, which, in sum, are more than treatment costs, pose an economic burden to society and patients. Work ability in RA appears to be multifactorial; symptoms such as pain, swelling, and stiffness play a major role, as these directly affect functional disability. Also, RA patients typica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 49 publications
1
4
0
Order By: Relevance
“…We found that GS was the most frequently reported symptom of frailty, suggesting that daily exercise is important to avoid frailty, as has been recommended by other investigators (22,23). RA patients have a weak grip force or upper extremity weakness due to joint damage (24); however, upper extremity weakness does not always figure into frailty assessment. We recommend that more attention should be paid to locomotive functions for RA patients.…”
Section: Discussionsupporting
confidence: 59%
“…We found that GS was the most frequently reported symptom of frailty, suggesting that daily exercise is important to avoid frailty, as has been recommended by other investigators (22,23). RA patients have a weak grip force or upper extremity weakness due to joint damage (24); however, upper extremity weakness does not always figure into frailty assessment. We recommend that more attention should be paid to locomotive functions for RA patients.…”
Section: Discussionsupporting
confidence: 59%
“…One hundred participants visiting the rheumatology outpatient clinic of the Kaiser Franz Josef Hospital in Vienna during their regularly scheduled visits were recruited for the purposes of this study [ 22 ]. Inclusion criteria were: age between 18 and 65 years; and fulfilled the RA diagnostic criteria according to the 2010 European League Against Rheumatism (EULAR) classification at the time of inclusion [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…This paper presents the results of a larger cross-sectional study in patients with from RA. The complete study protocol was previously published [ 22 ]. The aim of the present study was to determine the prevalence of problems with sleep and its association with disease activity, pain levels, inflammatory parameters, and functional disability in patients with RA.…”
Section: Introductionmentioning
confidence: 99%
“…This monocentric cross-sectional study was performed at the rheumatology outpatient clinic of the SMZ Süd Hospital (Vienna, Austria), from November 2015 to August 2016 [ 22 ]. This study was approved by the Medical Ethical Committee of the Gemeinde-Wien (EK 15-173-0915) and complied with the Declaration of Helsinki.…”
Section: Methodsmentioning
confidence: 99%